Answer:
Liam is right.
Explanation:
The transformation that demonstrate the congruence between these two triangles is the given one by Liam:
can be reflected over the y-axis to create
![\triangle EFD](https://img.qammunity.org/2020/formulas/mathematics/middle-school/761yfsme8zq9ze14tvppzr99fqld9zwl1g.png)
You can get this answer by observing the given graph. You can realize that one triangle is a reflection of the other across y-axis, because when this happens, the x-coordinates are changed by their opposite. There you can see that
x = -7 is changed to x' = 7
x = -3 is changed to x' = 3
x = -2 is changed to x' = 2
Therefore, the right transformation is the reflection accross y-axis given by Liam, he's right.